1990
DOI: 10.4102/abc.v20i2.927
|View full text |Cite
|
Sign up to set email alerts
|

Ordination as a tool for substantiating and interpreting floristic classifications: a case study

Abstract: Detrended Correspondence Analysis ordination is used as a tool for substantiating the authenticity of hierarchical syntaxa derived from a phytosociological classification of the vegetation of the Eastern Transvaal Escarpment in the Sabie area. Ecological interpretation of syntaxa is facilitated by superimposing environmental variables on axes of ordination. UITTREKSELOrdinasie deur middel van Ontneigde Ooreenstemmingsanalise is gebruik ter ondersteuning van die geldigheid van die hiërargiese sintaksons wat ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Based on initial field observations and a study in a similar environment (Deall & Theron 1990), elevation and geology were identified as being of major impor tance. Using six elevation classes, starting at 600 m asl and each spanning 200 m, and the 12 geological sub strates, a total of 51 elevation-geology combinations are present in the SGR.…”
Section: Landscape Diversitymentioning
confidence: 99%
“…Based on initial field observations and a study in a similar environment (Deall & Theron 1990), elevation and geology were identified as being of major impor tance. Using six elevation classes, starting at 600 m asl and each spanning 200 m, and the 12 geological sub strates, a total of 51 elevation-geology combinations are present in the SGR.…”
Section: Landscape Diversitymentioning
confidence: 99%